Deceptively normal MR in early infantile Krabbe disease. - Finelli, D A; Tarr, R W; Sawyer, R N; Horwitz, S J (American Journal of Neuroradiology, 1994)
The authors present two cases of 5-month-old children with early infantile Krabbe disease studied by CT and MR. Both infants had characteristic CT scans for the disease consisting of symmetric hyperdensity involving the cerebellum, thalami, caudate, corona radiata, and brain stem. One of the infants had a deceptively normal initial MR examination, with dramatic progression of the white-matter disease over the following 4 months.